Design, Synthesis and Evaluation of Schiff’s Bases of 4-Chloro-3-coumarin aldehyde as Antimicrobial Agents - Shriram Bairagi; Ashok Bhosale; Meenakshi N. Deodhar (E-Journal of Chemistry)
4-Chloro-2-oxo-2H-chromene-3-carbaldehyde (2) was reacted with different anilines in rectified spirit as solvent to yield a series of the title compounds i.e. 4-chloro-3-((substituted-phenylimino) methyl)-2H-chromen-2-one (3a-i). These compounds were charaterised on the basis of their spectral (IR, 1H NMR) data and evaluated for antimicrobial activity in vitro against gram positive and gram negative bacteria and fungi. Compound 3C was found to be most active with an MIC of 15 μg /mL against all the tested organisms.